THE ROLE OF LOCAL WISDOM "MANOKOK TABUAH" AS AN EARLY WARNING SYSTEM AGAINST FLOODING IN NAGARI SUNGAI LIKU, PESISIR SELATAN REGENCY - Nadhilah, Qoori; Alfisar, Muhammad Farras; Sitorus, Sonia Boru; Amelia, Anggi; Danuarta, Arga; Hendria, Viony (International Remote Sensing Applied Journal, 2025)
This research seeks to explore the role of the Manokok Tabuah system as a traditional early warning mechanism for flood disasters in Nagari Sungai Liku, assess its effectiveness in enhancing community preparedness, and examine its potential integration with modern technology. A descriptive qualitative approach was employed, utilizing data collection methods such as in-depth interviews, field observations, and documentation. Data were analyzed using the Miles and Huberman model, involving the stages of data reduction, data display, and conclusion drawing. The findings indicate that Manokok Tabuah serves not only as an effective culturally-based early warning tool but also fosters social cohesion within the community in the face of disasters. Although it has been largely replaced by modern sirens, the system retains significant cultural value. Therefore, combining traditional practices with modern technological approaches is considered essential for developing an adaptive and sustainable disaster mitigation system